2013
DOI: 10.1186/1742-9994-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Only distance matters – non-choosy females in a poison frog population

Abstract: BackgroundFemales have often been shown to exhibit preferences for certain male traits. However, little is known about behavioural rules females use when searching for mates in their natural habitat. We investigated mate sampling tactics and related costs in the territorial strawberry poison frog (Oophaga pumilio) possessing a lek-like mating system, where both sequential and simultaneous sampling might occur. We continuously monitored the sampling pattern and behaviour of females during the complete period be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 137 publications
(201 reference statements)
4
34
0
Order By: Relevance
“…In addition, sexual selection through nonrandom courtship within color morphs has been reported in O. pumilio (Reynolds & Fitzpatrick, 2007) and Ranitomeya (Twomey et al., 2014) and can possibly promote diversification of color among populations, while decreasing the variation within. However, this phenomenon seems highly dependent on the environmental context and genetic background of the frogs (Medina et al., 2013; Meuche, Brusa, Linsenmair, Keller, & Pröhl, 2013; Richards‐Zawacki et al., 2012; Twomey et al., 2014). A recent study reported an example of hybridization promoting new coloration and patterning between two close species O. histrionica and O. lehmanni (Medina et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sexual selection through nonrandom courtship within color morphs has been reported in O. pumilio (Reynolds & Fitzpatrick, 2007) and Ranitomeya (Twomey et al., 2014) and can possibly promote diversification of color among populations, while decreasing the variation within. However, this phenomenon seems highly dependent on the environmental context and genetic background of the frogs (Medina et al., 2013; Meuche, Brusa, Linsenmair, Keller, & Pröhl, 2013; Richards‐Zawacki et al., 2012; Twomey et al., 2014). A recent study reported an example of hybridization promoting new coloration and patterning between two close species O. histrionica and O. lehmanni (Medina et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that O. pumilio chooses a microhabitat to increase (or decrease) their conspicuousness as it relates to predator avoidance (Pröhl & Ostrowski ; Maan & Cummings ), and therefore, mate choice may be the result of spatial autocorrelation (Meuche et al. ). Additional studies will be necessary to better understand whether females actively choose males with similar coloration, or whether similarly colored pairs occur as a result of closeness and habitat choice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, female O. pumilio who are in contact with a male on a given day are highly likely to ultimately select that male to mate with (Meuche et al. ). Therefore, it was presumed that if a female interacted with a male for 15 min, a mating event was likely to occur.…”
Section: Methodsmentioning
confidence: 99%
“…For example, males might gain mating advantages from female preference for conspicuous colouration, which originally evolved in a non-sexual context to warn predators. However, under certain laboratory conditions, females of Dendrobates pumilio prefer brighter and possibly more toxic males [35], while in natural conditions females prefer the closest calling male [36].…”
Section: Discussionmentioning
confidence: 99%